Genetic parameters of resistance to Vibrio aestuarianus, and OsHV-1 infections in the Pacific oyster, Crassostrea gigas, at three different life stages. Issue 1 (December 2017) - Azéma, Patrick; Lamy, Jean-Baptiste; Boudry, Pierre; Renault, Tristan; Travers, Marie-Agnès; Dégremont, Lionel
Abstract Background In France, two main diseases threaten Pacific oyster production. Since 2008, Crassostrea gigas spat have suffered massive losses due to the ostreid herpesvirus OsHV-1, and since 2012, significant mortalities in commercial-size adults have been related to infection by the bacteriumVibrio aestuarianus . The genetic basis for resistance toV. aestuarianus and OsHV-1 and the nature of the genetic correlation between these two traits were investigated by using 20 half-sib sire families, each containing two full-sib families. For each disease, controlled infectious challenges were conducted using naïve oysters that were 3 to 26 months old. In addition, siblings were tested under field, pond and raceway conditions to determine whether laboratory trials reflected mortality events that occur in the oyster industry. Results First, we estimated the genetic basis of resistance toV. aestuarianus inC. gigas . Susceptibility to the infection was low for oysters in spat stage but increased with later life stages. Second, we confirmed a strong genetic basis of resistance to OsHV-1 infection at early stages and demonstrated that it was also strong at later stages. Most families had increased resistance to OsHV-1 infection from the spat to adult stages, while others consistently showed low or high mortality rates related to OsHV-1 infection, regardless of the life stage. Our third main finding was the absence of genetic correlations between resistance to OsHV-1 infection and resistance toV. aestuarianus infection. Conclusions Selective breeding to enhance resistance to OsHV-1 infection could be achieved through selective breeding at early stages and would not affect resistance toV. aestuarianus infection. However, our results suggest that the potential to select for improved resistance toV. aestuarianus is lower. Selection for dual resistance to OsHV-1 andV. aestuarianus infection inC. gigas might reduce the impact of these two major diseases by selecting families that have the highest breeding values for resistance to both diseases.